2020
DOI: 10.1111/dth.14193
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of melanoma bone metastasis: A multidisciplinary approach

Abstract: Bone is the fourth most common site of melanoma metastasis after lung, liver, and brain. Melanoma bone metastases typically occur in patients who already have widespread metastases in other organs. Current available approaches for bone metastases from melanoma include chemotherapy, radiotherapy, biological therapy, combination therapy, and surgery. In this narrative review, we describe the management of patients affected by melanoma bone metastases, discussing the diagnostic and treatment approaches as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Nodular melanoma is more common in males than females. It is often ulcerated with the tendency of more vertical growth than traditional radial growth [ 2 ]. Lentigo maligna melanoma correlates with long-term sun exposure and increasing age that may develop for decades before invading the papillary dermis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodular melanoma is more common in males than females. It is often ulcerated with the tendency of more vertical growth than traditional radial growth [ 2 ]. Lentigo maligna melanoma correlates with long-term sun exposure and increasing age that may develop for decades before invading the papillary dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is the fourth frequent distant metastatic organ. Melanoma bone metastasis usually occur in patients who already have widespread metastases in other organs [ 2 ]. Herein, we present a rare case of ALM lesion which was originally found in the base of right fifth toe plantar with multiple bone metastases but without any other organs involving.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of D16F7 mAb includes a marked inhibitory effect on the ability of melanoma to infiltrate bone marrow, reducing the levels of PlGF that can attract more VEGFR-1-expressing tumor cells. This finding is of particular relevance, given that bone is the fourth most common site of melanoma metastasis and that patients with multiple skeletal events have a dismal prognosis [ 40 , 41 ]. The results of in vitro studies indicated that D16F7 mAb was also able to induce a reduction in PlGF release in melanoma culture supernatants, likely contributing to a restrained tumor invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming these challenges requires a multidisciplinary approach combining innovative therapeutic strategies, imaging and diagnostic techniques advancements, and a comprehensive understanding of the BME ( 196 ). By addressing these challenges head-on, researchers and clinicians aim to improve outcomes for patients with bone-metastatic cancers, enhance the quality of life, and develop more effective treatment options tailored to the unique characteristics of this disease.…”
Section: Challenges In Bone-metastatic Cancer Treatmentmentioning
confidence: 99%